2019
DOI: 10.3928/02793695-20190528-01
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Arab Adolescents: A Qualitative Study

Abstract: Depression rates among Arab adolescents are expected to rapidly increase necessitating research-based data to aid in planning effective strategies to implement primary prevention and treatment interventions. The current study aimed to capture Jordanian adolescents' experience of depression, identify perceived contributing factors, and assess their attitudes toward depression interventions. An exploratory, qualitative design was used to collect data from 92 participants (age range = 14 to 17) through 12 focus g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 30 publications
3
24
0
Order By: Relevance
“…Within a school community, adolescent female mental health issues may go undetected if compared to a physical health issue for instance, particularly when there is a lack of trained school workers, nurses, school and educational psychologists or when there is limited awareness about mental health symptoms among this age group. In Jordan, adolescents who revealed depression related symptoms were unaware and uncertain that their symptoms were associated with depression (Dardas, Shoqirat, et al, 2019). This suggests that depression and anxiety among adolescents may go unrecognized and treatment be delayed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within a school community, adolescent female mental health issues may go undetected if compared to a physical health issue for instance, particularly when there is a lack of trained school workers, nurses, school and educational psychologists or when there is limited awareness about mental health symptoms among this age group. In Jordan, adolescents who revealed depression related symptoms were unaware and uncertain that their symptoms were associated with depression (Dardas, Shoqirat, et al, 2019). This suggests that depression and anxiety among adolescents may go unrecognized and treatment be delayed.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that depression and anxiety among adolescents may go unrecognized and treatment be delayed. Further, the adolescents in Jordan reported low support from teachers in regards of problematic symptoms of mental issues, such as lack of concentration or irritability, which were often treated with discipline and punishment (Dardas, Shoqirat, et al, 2019). This is reinforced by another study of Jordanian adolescents with higher depression scores who indicated that they were less likely to actively seek professional sources for help with depression symptoms (Dardas, Silva, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such loss from war and conflict has become all too familiar in recent times. Several studies consider the loss of loved ones a reason for depression and suggest a strong positive correlation between loss and depression rates (Clements et al, 2004;Dardas et al, 2019;Hickman, 1994). The main character of the story, 9-year-old Zahraa, loses her parents and moves to live with her father's cousin and his wife in Alexandria, Egypt.…”
Section: Coping Mechanisms For Dealing With Loss and Depressionmentioning
confidence: 99%
“…In [29,30], a survey was conducted in a high school in Saudi Arabia and the prevalence of depression between the students was 17% and 33.4%. Besides, the survey achieved by [24] was carried out in Jordan with a sample of 3,292 adolescents, also another research with 92 adolescents [31,32], it presents a systematic review of studies conducted on the UAE population relating to depression.…”
Section: Literature Reviewmentioning
confidence: 99%